Perancangan Perabot Edukasi Dengan Pendekatan Pembelajaran Montessori Pada Vision School Sidoarjo - Cecilia Widjaja (Intra, 2017)
The existing school interiors nowadays is more interesting and fun, because it is influenced by the current learning system which changes from teacher-oriented system to student-oriented system. This comprehension arises because of the idea that learning is a natural process of human beings, learning is only mediated by the teacher but overall it is a process that is natural, so it must emerge from within oneself. Therefore, the design of this educational furniture is one of the strategies to optimize the learning process. This problem formulation of this design is about how to design interactive and educative furniture which effectively and efficiently functions in Vision School classroom which has limited space, based on Montessori learning.The methods used to objectify the educational furniture are Montessori teaching methods and FUSE concept (Fun, Unique, Save, Educative). The purpose of this design is to provide a pleasant and comfortable interior space to optimize the teaching and learning process at Vision School Sidoarjo. The product of this thesis are, 3 educational furniture, each equipped with reading ,creativity ,and game feature which are based on Montessori learning to provide experience of fun learning. The benefit of this design is to provide insight in the field of education and furniture design about how to design educational furniture that helps to optimize the learning process of children using educational methods which is supported by FUSE concept.